Curcumin-loaded multi-valent ligands conjugated-nanoparticles for anti-inflammatory activity - Phongpradist,R. (IJPPS, 2015)
© 2015, International Journal of Pharmacy and Pharmaceutical Science. All rights reserved. Objective: The present study aims to develop curcumin-loaded muti-valent ligands conjugated-nanoparticlesfor targeted cell and study the biological activities including anti-inflammatory activity and kinetic cellular uptake. Methods: Curcumin encapsulated PLGA nanoparticles were formulated by solvent displacement method. The cIBR and cLABL peptides were conjugated on the surface of PLGA nanoparticles using carbodiimide reaction to produce curcumin encapsulated cIBR-cLABL-nanoparticles (cIBR-cLABL-NPs). The expression of LFA-1 and ICAM-1 on the membrane of U937 cells were determined by flow cytometry. Kinetic binding and internalization profile of cIBR-cLABL-NPs and untargeted nanoparticles were also investigated by flow cytometry. Safety profile on PBMC and cytotoxicity profile on U937 cells were evaluated using the MTT assay. Anti-inflammatory activity was determined using aprotein denaturation method. Results: The densities of cIBR and cLABL peptide on the surface of PLGA nanoparticles were 22.0±4.4 and 19.6±2.8 pmol/cm2, respectively. The particle size and total surface area of PLGA were 256.1 nm and 0.038 m2/g. The result showed that U937 cells expressed both LFA-1 and ICAM-1 proteins on their membranes indicating the possibility to use U937 cells as a targeted cell. According to the kinetic binding and internalization profiles, the cellular uptake of cIBR-cLABL-NPs was significantly higher than that of untargeted-NPs at all-time points indicating the specific uptake of cIBR-cLABL-NPs to target cell. Moreover, the rate of binding and internalization interpreted by the slope of linear regression of cIBR-cLABL-NPs was more rapid than that of untargeted-NPs. The MTT assay revealed the safety on human PBMC of cIBR-cLABL-NPs. The IC50of free curcumin and curcumin-loaded cIBR-cLABL-NPs were 0.13 and 2.27 μg/ml, respectively. Protein denaturation assay presented the concentration dependence inhibition of protein denaturation by curcumin and cIBR-cLABL-NPs indicating anti-inflammatory activities of free curcumin and encapsulated curcumin. Conclusion: cIBR-cLABL-nanoparicles increased the quantity of binding, rate of binding, and the internalization by target cells with safety profile on human PBMC. Moreover, the biological activity of encapsulating agent was maintained. Therefore, it could be used as a drug delivery system for encapsulating anti-infalmmatory agents.